Bax and the ‘Celtic North’ (Journal of the Society for Musicology in Ireland, 2013)
Scholars of Arnold Bax have long acknowledged the influence of the Irish Literary Revival on the composer’s compositional output up to about 1920, of Sibelius from the late 1920s onwards, and of the continuity of styles between these two periods. In this article I argue that this continuity relies on what Bax draws from early Yeats, which is less Celtic mythology or folklore than a particular way of imagining nature; that Bax’s use as a compositional stimulus of what he called the ‘Celtic North’ (essentially the landscapes of western Ireland and north-western Scotland) had parallels in the literature and art of 1920s Ireland; and that the ‘Celtic North’ offers a means of critiquing inter-war English pastoralism, which has traditionally been associated with what Alun Howkins, after Hilaire Belloc, has called the ‘South Country’. Bax thus offers a musical engagement with nature that is essentially dystopian, sublime and (within the discourse of British pastoralism) non-Anglo Saxon.